Research Progress on Risk Assessment and Management and Control of Dike Engineering Danger - JIANG Shuihua; CHEN Yingxia; XIONG Wei; LI Yuwei; CHANG Zhilu; LI Jinhui; LI Wenhuan (Renmin Zhujiang)
Dike is an important facility to prevent flood disasters in the area of lakes and plain rivers. There are lots of serious loss consequences when dike engineering is in danger and causes destruction. Therefore, risk assessment, as well as management and control of dike engineering danger have been given great importance all over the world. However, the uncertain factors such as dike material properties, earthquakes, and extremely heavy rainfall in dike engineering systems are not quantitatively characterized insufficiently, and the understanding of occurrence environments where dike engineering danger exists is not clear. As a result, the mechanism and evolution process of dike engineering danger are not clarified. Besides, the risk assessment methods of dike engineering danger are still mainly semi-qualitative and semi-quantitative, lacking corresponding comprehensive quantitative assessment methods and measuring standards for the consequences of dike engineering danger, resulting in poor effect of risk management and control measures for dike engineering danger. In view of this, the literature and field investigation were conducted in five aspects: identification and characterization of the occurrence environment for dike engineering danger, disaster mechanism and evolution processes of dike engineering danger, consequence analysis of dike engineering danger, risk assessment of dike engineering danger, and risk management and control of dike engineering danger. Then, the overseas and Chinese research and existing problems in the above five aspects were summarized. Furthermore, the prospective key research contents of risk assessment, as well as management and control of dike engineering danger were concluded. The research results are expected to provide important ideas and theoretical support for scientifically revealing the disaster mechanism of dike engineering danger, putting forward a practical quantitative risk assessment method for dike engineering danger, and constructing a risk-based informatization and standardized information management and control system for dike engineering.